Loss of A-type lamin expression compromises nuclear envelope integrity in breast cance - CAPO-CHICHI, D. CALLINICE (My University, 2011)
Through advances in technology, the genetic basis of cancer has been investigated at the genomic level, and many fundamental questions have begun to be addressed. Among several key unresolved questions in cancer biology, the molecular basis for the link between nuclear deformation and malignancy has not been determined. Another hallmark of human cancer is aneuploidy; however, the causes and consequences of aneuploidy are unanswered and are hotly contested topics. We found that nuclear lamina proteins lamin A/C are absent in a significant fraction (38%) of human breast cancer tissues. Even in lamin A/C-positive breast cancer, lamin A/C expression is heterogeneous or aberrant (such as non鄄 nuclear distribution) in the population of tumor cells, as determined by immunohistology and immunofluorescence microscopy. In most breast cancer cell lines, a significant fraction of the lamin A/C- negative population was observed. To determine the consequences of the loss of lamin A/C, we suppressed their expression by shRNA in non鄄 cancerous primary breast epithelial cells. Down鄄 regulation of lamin A/C in breast epithelial cells led to morphological deformation, resembling that of cancer cells, as observed by immunofluorescence microscopy. The lamin A/C-suppressed breast epithelial cells developed aneuploidy as determined by both flow cytometry and fluorescence in situ hybridization. We conclude that the loss of nuclear envelope structural proteins lamin A/C in breast cancer underlies the two hallmarks of cancer鄄 aberrations in nuclear morphology and aneuploidy. Key
Keywords: Nuclear envelope; lamin A/C; aneuploidy; polyploidy; nuclear grade; nuclear morphology; breast cancer